Antithrombotics in thrombosis and cancer - Mousa, S. A. (Hämostaseologie, 2005)
Many cancer patients have a hypercoagulable state, with recurrent thrombosis due to the impact of cancer cells and chemotherapy or radiotherapy on the coagulation cascade. Studies have demonstrated that unfractionated heparin (UFH) or its low molecular weight fractions interfere with various processes involved in tumour growth and metastasis. These include fibrin formation; binding of heparin to angiogenic growth factors, such as basic fibroblast growth factor (FGF2) and vascular endothelial growth factor (VEGF); modulation of tissue factor; and perhaps other more important modulatory mechanisms, such as enhanced tissue factor pathway inhibitor (TFPI) release and inhibition of various matrix-degrading enzymes. Clinical trials have suggested a clinically relevant effect of low molecular weight heparin (LMWH), as compared to UFH, on the survival of cancer patients with deep vein thrombosis. Similarly, the impact of warfarin on the survival of cancer patients with thromboembolic disorders was demonstrated. Studies from our laboratory demonstrated a significant role for LMWH, warfarin, anti-VIIa, and LMWH-releasable TFPI on the regulation of angiogenesis, tumour growth, and tumour metastasis. Thus, modulation of tissue factor/VIIa non-coagulant activities by LMWH, warfarin, anti-VIIa, or TFPI might be a useful therapeutic method for the inhibition of angiogenesis associated with human tumour growth and metastasis. Additionally, antiplatelet drugs could have an impact on tumour metastasis, and the combination of antiplatelets and anticoagulants at adjusted doses might provide greater benefits to cancer patients.
Keywords: Acetylsalicylic acid; GPIIb/IIIa antagonists; heparin; LMWH; TF/VIIa; TFPI; FGF2; VEGF; cancer; angiogenesis; thrombosis